Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(=\left(2-\sqrt{3}\right)\left(\sqrt{3}+1\right)\sqrt{2}\left(\sqrt{2+\sqrt{3}}\right)\)
\(=\left(2-\sqrt{3}\right)\left(\sqrt{3}+1\right)\sqrt{2\left(2+\sqrt{3}\right)}\)
\(=\left(2\sqrt{3}+2-3-\sqrt{3}\right)\sqrt{4+2\sqrt{3}}\)
\(=\left(\sqrt{3}-1\right)\sqrt{3+2\sqrt{3}+1}\)
\(=\left(\sqrt{3}-1\right)\sqrt{\left(\sqrt{3}\right)^2+2\cdot\sqrt{3}\cdot1+1^2}\)
\(=\left(\sqrt{3}-1\right)\sqrt{\left(\sqrt{3}+1\right)^2}\)
\(=\left(\sqrt{3}-1\right)|\sqrt{3}+1|\)
\(=\left(\sqrt{3}-1\right)\left(\sqrt{3}+1\right)\)
\(=\left(\sqrt{3}\right)^2-1^2\)
\(=3-1\)
\(=2\)
a/ \(2\sqrt{40\sqrt{12}}-2\sqrt{\sqrt{75}}-3\sqrt{5\sqrt{48}}=2\sqrt{4.2.5\sqrt{4.3}}-2\sqrt{\sqrt{25.3}}-3\sqrt{5\sqrt{16.3}}\)
= \(2.2\sqrt{2.5.2\sqrt{3}}-2\sqrt{5\sqrt{3}}-3\sqrt{5.4\sqrt{3}}=4.2\sqrt{5\sqrt{3}}-2\sqrt{5\sqrt{3}}-3.2\sqrt{5\sqrt{3}}\)
= \(\sqrt{5\sqrt{3}}\left(8-2-6\right)=\sqrt{5\sqrt{3}}.0=0\)
b/ \(2\sqrt{8\sqrt{3}}-2\sqrt{5\sqrt{3}}-3\sqrt{20\sqrt{3}}=2\sqrt{2.4\sqrt{3}}-2\sqrt{5\sqrt{3}}-3\sqrt{4.5\sqrt{3}}\)
= \(4\sqrt{2\sqrt{3}}-2\sqrt{5\sqrt{3}}-6\sqrt{5\sqrt{3}}=4\sqrt{2\sqrt{3}}-8\sqrt{5\sqrt{3}}\)
=\(\sqrt{3}-1+2-\) \(\sqrt{3}=1\)
b.=\(\frac{2+\sqrt{3}-2+\sqrt{3}}{2^2-3}=2\sqrt{3}\)
b, \(\frac{\sqrt{3}}{2+\sqrt{3}}-\frac{\sqrt{3}}{2-\sqrt{3}}\) = \(\frac{\sqrt{3}\left(2-\sqrt{3}\right)-\sqrt{3}\left(2+\sqrt{3}\right)}{\left(2+\sqrt{3}\right)\left(2-\sqrt{3}\right)}\)=\(\frac{2\sqrt{3}-3-2\sqrt{3}-3}{\left(2+\sqrt{3}\right)\left(2-\sqrt{3}\right)}\)=\(\frac{-6}{4-3}\)=-6
c,\(\frac{2}{\sqrt{5}-2}-\frac{2}{\sqrt{5}+2}\)=\(\frac{2\left(\sqrt{5}+2\right)-2\left(\sqrt{5}-2\right)}{\left(\sqrt{5}+2\right)\left(\sqrt{5}-2\right)}\)=\(\frac{2\sqrt{5}+4-2\sqrt{5}+4}{\sqrt{5}^2-2^2}\)=\(\frac{8}{1}\)=8
\(\frac{\sqrt{9-4\sqrt{5}}}{2-\sqrt{5}}\)
= \(\frac{\sqrt{2^2-2\sqrt{5}2+\sqrt{5^2}}}{2-\sqrt{5}}\)
= \(\frac{\sqrt{\left(2-\sqrt{5}\right)^2}}{2-\sqrt{5}}\)
= \(\frac{\sqrt{5}-2}{2-\sqrt{5}}\)
= -1
Chúc bạn làm bài tốt :)
Đặt A= .....
A\(^2\)= \(2+\sqrt{3}\)+\(2-\sqrt{3}\)+ \(2\sqrt{\left(2+\sqrt{3}\right)\left(2-\sqrt{3}\right)}\)
A\(^2\)= 4 + \(2\sqrt{2^2-\left(\sqrt{3}\right)^2}\)
A\(^2\)= 4 + \(2\sqrt{4-3}\)
A\(^2\)= 4 +2=6
Vây A=\(\sqrt{6}\)
Cảm ơn bn nhiều nha